Implementasi Hukum Perlindungan Pekerja Perempuan Dalam Ketenagakerjaan - M. Farid Al Zaki (LPPM Universitas Pahlawan Tuanku Tambusai, 2026)
Given the ongoing progress and changes regarding gender equality, protecting female employees in the workplace has become crucial. To ensure that women can work safely, free from discrimination, and with rights equal to those of men, adequate legal protection is essential. Various policies and procedures are incorporated into the legal framework for women in the labor market, aiming to uphold the rights of female employees, eliminate gender discrimination, and foster a safe and healthy work environment. The primary objective of these measures is to promote workplace gender equality and ensure fair and equal access to employment, social protection, professional growth, and well-being for women. Qualitative research is understood as a method utilizing descriptive data—specifically written or spoken language from observable individuals and participants. This qualitative approach is employed to explain and analyze phenomena concerning individuals or groups, events, social dynamics, attitudes, beliefs, and perceptions. Legal protection for workers is regulated under Law Number 11 of 2020 concerning Job Creation.